On symmetric (78,22,6) designs and related self-orthogonal codes - Crnkovic, Dean; Danilovic, Doris Dumicic; Rukavina, Sanja (Utilitas Mathematica, 2018)
We describe a method for constructing 2-designs admitting a solvable automorphism group, and construct new symmetric (78,22,6) designs, Until now, only five symmetric (78,22,6) designs were known. In this paper we show that, up to isomorphism, there are at least 413 symmetric (78,22,6) designs, 412 of them having Ze as an automorphism group. Further, we show that up to isomorphism there is exactly one symmetric (78,22,6) design admitting an automorphism group isomorphic to Frob$g x Z2, namely the design constructed by Zvonimir Janko and Tran van Trung. Thus, there is no (78,22,6) difference set in the group Frobw x Zi. We study binary linear codes spanned by the incidence matrices of the constructed designs. Further, extending previous results on codes obtained from orbit matrices of 2-designs, we show that under certain conditions both fixed and nonfixed part of an orbit matrix span a self-orthogonal code over the finite field Fpn or over the ring Zm- We construct self-orthogonal codes over Z4 spanned by orbit matrices of symmetric (78,22,6) designs. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.